Expressions of Cultural Communication in the Use of Songket in Palembang Wedding Customs - Widiyanarti, Tantry; Shahreza, Mirza; Irwan, Irwan; Felia, Vira Wera (International Journal of Education, Vocational and Social Science, 2022)
As one of the Intangible Cultural Heritage (WBTb) owned by Indonesia, songket, especially Palembang's songket, is a cultural heritage that must be preserved. In addition to having noble values and high aesthetics, when worn in formal events such as weddings, songket is also a medium for conveying messages that are shown in Palembang wedding customs. The purpose of this study is to find out how the symbolic form of songket communication , its meaning conveyed in Palembang wedding customs and what kind of expressions it showed, with descriptive-qualitative method. The result of this study is that songket is used to communicate symbolically at several stages in Palembang wedding customs, such as in the mandik , n yenggong/ berasan , proposing & m utus k ato and also in mupload (wedding ceremony). Symbolic forms and expressions that show are happiness, sadness, interest, approval and also appreciation and prestige. Furthermore, there's an invention that shows songket in its manufacture gets innovation by using Machine Weaving Tools (ATM), thanks to this innovation other creations from songket have been created, such as songket souvenirs.